Anisotropic Charged Fluid Sphere in Isotropic Coordinates. (2nd September 2014) - Pant, Neeraj; Pradhan, N.; Singh, Ksh. Newton
Abstract : We have presented a class of charged superdense star models, starting with a static spherically symmetric metric in isotropic coordinates for anisotropic fluid by considering Hajj-Boutros-(1986) type metric potential and a specific choice of electrical intensity E and anisotropy factor Δ which involve charge parameter K and anisotropy parameter α . The solution is well behaved for all the values of Schwarzschild compactness parameter u lying in the range 0 < u ≤ 0.2086, for all values of charge parameter K lying in the range 0.04 ≤ K ≤ 0.111 , and for all values of anisotropy parameter α lying in the range 0.016 ≥ α ≥ 0 . With the increase in α, the values of K and u decrease. Further, we have constructed a superdense star model with all degree of suitability. The solution so obtained is utilized to construct the models for superdense star like neutron stars ρ b = 2.7 × 10 14 g / c m 3 and strange quark stars ρ b = 4.6888 × 10 14 g / c m 3 . For K = 0.06 and α = 0.01, the maximum mass of neutron star is observed as M = 1.53 M ⊙ and radius R = 11.48 km . Further for strange quark stars M = 1.16 M ⊙ and R = 8.71 km are obtained.